KAJIAN PENERAPAN MANAJEMEN ASET DAERAH WISATA DALAM PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN PESISIR SELATAN - Febrimen Herista (Ensiklopedia of Journal, 2019)
The results of the research conducted, discovered that: 1). District asset controlling system has significant positive influence to the empowerment of district asset; 2) District asset accounting system has non significant positive influence to the empowerment of district asset; 3) The empowerment of district asset has non significant positive influence to the districts asset performance; 4) The performance of district asset has significant positive influence to the district’s genuine revenue; 5) District asset accounting has significant positive influence to district asset controlling system; 6) District asset controlling system has non significant positive influence to district asset performance; 7) District asset accounting system has non significant positive influence to the district asset performance; 8)District asset controlling system has non significant positive influence to district actual income; 9) accounting system of district asset has non significant positive influence to district actual income.